Regional perceptions of the 'ejque': Exploring attitudes toward velarized /s/ outside of Madrid - Wright, Robyn (Borealis – An International Journal of Hispanic Linguistics, 2021)
This paper explores the language attitudes of listeners from six different regions of Spain, Asturias, Castile and León, Castile-La Mancha, the Canary Islands, Catalonia and the Balearic Islands, towards a nonsibilant variant of coda /s/, the velarized /s/. This velar pronunciation, known by some as the ejque madrileño, has previously been found to index a Madrid identity for Madrileño listeners, though the traits ascribed such a speaker are quite negative. The current paper finds that like Madrileños themselves, participants from Asturias and Castile and León also associate velarized /s/ with Madrid. Participants from Castile-La Mancha, the Canary Islands, Catalonia and the Balearic Islands do not consider the velarized variant to be Madrileño. Furthermore, differing judgments of the nonsibilant /s/ are found among the regions tested, with participants from Catalonia and the Balearic Islands showing the most negative judgments while participants from Castile-La Mancha show no negative variable effect in their judgments. It is found that all of these out-group listeners do not show as severe of judgments as those seen by in-group members (Madrilenos themselves) in previous literature.